Giving Reasons A Linguistic-Pragmatic Approach to Argumentation Theory - Bermejo Luque, Lilian; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
This book provides a new, linguistic approach to Argumentation Theory. Its main goal is to integrate the logical, dialectical and rhetorical dimensions of argumentation in a model providing a unitary treatment of its justificatory and persuasive powers. This model takes as its basis Speech Acts Theory in order to characterize argumentation as a second-order speech act complex. The result is a systematic and comprehensive theory of the interpretation, analysis and evaluation of arguments. This theory sheds light on the many faces of argumentative communication: verbal and non-verbal, monological and dialogical, literal and non-literal, ordinary and specialized. The book takes into consideration the major current comprehensive accounts of good argumentation (Perelman$1 (Bs New Rhetoric, Pragma-dialectics, the ARG model, the Epistemic Approach) and shows that these accounts have fundamental weaknesses rooted in their instrumentalist conception of argumentation as an activity oriented to a goal external to itself. Furthermore, the author addresses some challenging meta-theoretical questions such as the justification problem for Argumentation Theory models and the relationship between reasoning and arguing.s
Preface -- I Argumentation and Its Study -- II Why Do We Need a New Theory of Argumentation? -- III Acts of Arguing -- IV The Logical Dimension of Argumentation -- V The Dialectical Dimension of Argumentation -- VI The Rhetorical Dimension of Argumentation -- VII Argumentation Appraisal -- References.
Keywords: Linguistics; Genetic epistemology; Logic; Linguistics -- Philosophy; Law -- Philosophy; Linguistics; Linguistics (general).; Logic; Epistemology; Law Theory/Law Philosophy; Learning & Instruction; Philosophy of Language